2019
DOI: 10.1002/adsc.201900450
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Umpolung Type‐II Cyclization of Allylic Carbonate‐Aldehydes Leading to 3‐Methylenecycloalkanol Derivatives

Abstract: Palladium‐catalyzed umpolung type‐II cyclization of allylic carbonate‐aldehydes leading to 3‐methylenecycloalkanol derivatives was developed. The formate reductant was effective for the cyclization without causing a reduction of the η3‐allylpalladium intermediate. One‐pot decarboxylative allylation of aldehyde‐containing malonate with 2‐[(acetyloxy)methyl]‐2‐propenyl methyl carbonate followed by the cyclization of the allyl acetate‐aldehyde formed in situ was also achieved. The high diastereoselectivities obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…In addition, deuterated phenylpropene d ‐ 2 a delivered d ‐ 4 a′ as expected. Moreover, as stated by Tsukamoto, employing ammonium formate as the reducing reagent also significantly improved the catalytic transformation of MBH carbonate 3 b and allylic carbonate 1 a (Scheme 2b) [5d,e] . These experiments demonstrated that the initial formed electrophilic η 3 ‐allylpalladium complex I would directly engage in the umpolung allylation process, probably via isomerization to nucleophilic η 1 ‐allylpalladium complex III .…”
Section: Resultssupporting
confidence: 52%
“…In addition, deuterated phenylpropene d ‐ 2 a delivered d ‐ 4 a′ as expected. Moreover, as stated by Tsukamoto, employing ammonium formate as the reducing reagent also significantly improved the catalytic transformation of MBH carbonate 3 b and allylic carbonate 1 a (Scheme 2b) [5d,e] . These experiments demonstrated that the initial formed electrophilic η 3 ‐allylpalladium complex I would directly engage in the umpolung allylation process, probably via isomerization to nucleophilic η 1 ‐allylpalladium complex III .…”
Section: Resultssupporting
confidence: 52%
“…Finally, transmetalation of J with (triisopropylsilyl)ethynyltributylstannane followed by reductive elimination from K yields L. Notably, an interesting mechanistic feature of this process is the umpolung reactivity of π-allylpalladium species, which undergoes nucleophilic allylation with aldehydes without the aid of external stoichiometric metallic reagents such as Et 2 Zn or Et 3 B as reducing agents. [19]…”
Section: Palladium-catalyzed Three-component Reaction Involving Sp 2 à Sp Couplingmentioning
confidence: 99%
“…Interestingly, enantioselective intramolecular umpolung cyclization proceeded without the aid of stoichiometric metallic reagents (Scheme 1c). [19] In addition to the asymmetric umpolung allylation reactions, this strategy was successfully extended to the palladium-catalyzed carboxylation of allylic alcohols under a CO 2 atmosphere (1 atm). [20] In particular, both the electrophilic and nucleophilic characteristics of the allyl counterparts can be incorporated in allylpalladium complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonamide 4aa (R = Ts) of the allyl aminoalcohol was chosen as the coupling partner owing to the stability of the target enamine, which was prepared according to the literature from ethyl 2-(hydroxymethyl)-2-propenoate in three steps 19 , 20 . While Cu-catalyzed selective N -arylation or O -arylation conditions of aminoalcohols have been reported to date 12 , 14 17 , a selective arylation or alkenylation between sulfonamides and alcohols has not been investigated.…”
Section: Resultsmentioning
confidence: 99%